Cytosolic calcium, hydrogen peroxide and related gene expression and protein modulation in Arabidopsis thaliana cell cultures respond immediately to altered gravitation: parabolic flight data. (22nd July 2013) - Hausmann, N.; Fengler, S.; Hennig, A.; Franz‐Wachtel, M.; Hampp, R.; Neef, M.
Abstract: Callus cell cultures of Arabidopsis thaliana (cv. Columbia) were exposed to parabolic flights in order to assess molecular, short‐term responses to altered gravity fields. Using transgenic cell lines, hydrogen peroxide (H2 O2 ) and cytosolic Ca 2+ were continuously monitored. In parallel, the metabolism of samples was chemically quenched (RNAlater, Ambion for RNA; acid/base for NADPH, NADP) at typical stages of a parabola [1  g before pull up; end of pull up (1.8  g ), end of microgravity (20 s) and end of pull out (1.8  g )]. Cells exhibited an increase in both Ca 2+ and H2 O2 with the onset of microgravity, and a decline thereafter. This behaviour was accompanied by a decrease of the NADPH/NADP redox ratio, indicating Ca 2+ ‐dependent activation of a NADPH oxidase. Microarray analyses revealed concomitant expression profiles. At the end of the microgravity phase, 396 transcripts were specifically up‐, while 485 were down‐regulated. Up‐regulation was dominated by Ca 2+ ‐ and ROS‐related gene products. The same material was also used for analysis of phosphopeptides with 2‐D SDS PAGE. Relevant spots were identified by liquid chromatography–MS. With the exception of a chaperone (HSP 70‐3), hypergravity (1.8  g ) and microgravity modified different sets of proteins. These are partly involved in primary metabolism (glycolysis, gluconeogenesis, citrate cycle) and detoxification of ROS. Taken together, these data show that both gene expression and protein modulation jointly respond within seconds to alterations in the gravity field, with a focus on metabolic adaptation, signalling and control of ROS.